2022
DOI: 10.1021/acsaem.2c03138
|View full text |Cite
|
Sign up to set email alerts
|

Antibonding p-d and s-p Hybridization Induce the Optimization of Thermal and Thermoelectric Performance of MGeTe3 (M = In and Sb)

Abstract: Manipulation of phonon transport is the key to optimizing the overall energy conversion efficiency of thermoelectric materials. In this work, we demonstrate that the antibonding hybridization resulting from elemental substitution can weaken the interatomic interactions, which in turn enhances the structural anharmonicity and hinders the heat conduction of layered ABTe 3 (ABSe 3 ) (A = Al, Ga, In, As, and Sb; B = Si and Ge) compounds. It is revealed that the filled antibonded p-d state of GaSiTe 3 (GaSiSe 3 ) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…The development of modern computational approaches, along with rapid growth in high-performance computational architectures, makes it more routine to compute phonon transport properties of materials during the past decade. Extensive studies have been focused on exploring various mechanisms, namely, rattling, , lone-pair, atomic mass, bonding hierarchy, , interplay among them, , , through sublattice alloying, , and designing principles have been proposed through chemical bonding. to achieve low lattice thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The development of modern computational approaches, along with rapid growth in high-performance computational architectures, makes it more routine to compute phonon transport properties of materials during the past decade. Extensive studies have been focused on exploring various mechanisms, namely, rattling, , lone-pair, atomic mass, bonding hierarchy, , interplay among them, , , through sublattice alloying, , and designing principles have been proposed through chemical bonding. to achieve low lattice thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we focus on a chemical bonding signature: highest-occupied valence bands with a strong anti-bonding character in a semiconductor. Recent studies have suggested that anti-bonding chemical bonds are closely related to ultralow thermal conductivities in a range of materials. The advantage of using the anti-bonding character of the highest-occupied valence band as a descriptor is that it can be efficiently analyzed using the crystal orbital Hamilton populations (COHP) method, , which only requires ground-state density functional theory (DFT) calculations. This method can be applied to any inorganic crystal structure and requires only basic structural and compositional information as input and minimal time and computing resources.…”
Section: Introductionmentioning
confidence: 99%
“…14 On the other hand, weakening the bonding strength through antibonding hybridization was identified as another effective method to improve heat transport. 15 For example, the intrinsically ultralow lattice thermal conductivity in CuBiI 4 can be attributed to the presence of robust p−d antibonding interactions between copper and iodine, which leads to the emergence of low-energy localized optical modes and suppresses the propagation of heat-carrying acoustic phonons. 16 Acharyya et al suggest that the presence of antibonding states weakens the bonds and induces soft elasticity, which, together with Cs rattling, results in an intrinsically ultralow κ L in all-inorganic halide perovskite Cs 3 Bi 2 I 9 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, significant advancements have been achieved in the exploration of TE candidates characterized by strong anharmonicity, such as SnSe, BiCuSeO, and Sb 2 Si 2 Te 6 . On the other hand, weakening the bonding strength through antibonding hybridization was identified as another effective method to improve heat transport . For example, the intrinsically ultralow lattice thermal conductivity in CuBiI 4 can be attributed to the presence of robust p–d antibonding interactions between copper and iodine, which leads to the emergence of low-energy localized optical modes and suppresses the propagation of heat-carrying acoustic phonons .…”
Section: Introductionmentioning
confidence: 99%